Analysis of spiroplasma proteins: contribution to the taxonomy of group IV spiroplasmas and the characterization of spiroplasma protein antigens. - Mouches, C. (Yale Journal of Biology and Medicine, 1983)
Spiroplasma strains of group IV were compared by two-dimensional protein analyses on polyacrylamide gels. Although considerable diversity was evident, the assemblages studied were less heterogeneous than the known strains of group I. Two electrophoretic techniques were used to identify spiroplasma proteins that had been used to immunize rabbits. These included monoclonal antibodies prepared against Spiroplasma citri. In the first technique, protein antigens were purified by immunoaffinity chromatography, then identified with SDS-PAGE. In the second technique, spiroplasma proteins were first separated by SDS-PAGE, then antigens were identified by antibody binding to blot-transferred proteins. Finally, two-dimensional protein electrophoresis has been used as a source of immunogens to characterize monospecific antibodies against individual S. citri proteins.